OPTIMASI IMPLEMENTASI SOFT SKILL BERBASIS TEKNOLOGI INFORMASI BAGI GURU KEJURUAN PADA PENDIDIKAN VOKASI - Lili Suryati; Wakhinuddin Simatupang; Dedy Irfan; Mukhlidi Muskhir (Universitas Lancang Kuning, 2022)
Abstract This research is a research with a combination method that aims to optimize the implementation of soft skills based on Information and Communication Technology (ICT) in vocational education. The results of this study need to optimize the improvement of soft skills implementation in the era of revolution 4.0 in the realm of vocational education. Acquisition The results of quantitative calculations obtain the result that Intrapersonal Ability is as large as 54,13 % sufficient category and Interpersonal Ability obtained Respondent Achievement Rate of 65.65% is in the Good category. The results of optimizing the implementation of ICT-based soft skills in vocational teachers in the 4.0 revolution era with a percentage of 59.89 are in the sufficient category. The ability of a teacher interpersonally includes the teacher having good responsibility in the process of carrying out tasks at school, the teacher has good integrity, and the teacher has confidence in himself and others. Meanwhile, the interpersonal skills possessed by the teacher include the ability to adapt to others or colleagues and others at school, have the ability to negotiate with others, be able to work with teams and have a leadership spirit. In addition, efforts that can be made to optimize ICT-based teacher competencies can be done by increasing the Role of Teachers using digitalization in the Revolutionary Era 4.0 by providing challenges to teachers in developing professionalism and pedagogical competence of teachers in schools and increasing Teacher Competence in Mastering Learning Strategies by trying to connect science and technology into everyday life.